Batch to continuous photocatalytic degradation of phenol using TiO2 and Au-Pd nanoparticles supported on TiO2. Issue 5 (October 2018) - Yilleng, Moses T.; Gimba, Emmanuel C.; Ndukwe, George I.; Bugaje, Idris M.; Rooney, David W.; Manyar, Haresh G.
Abstract: A series of Au-Pd/TiO2 catalysts were synthesized in different weight % using sol-immobilization method. Of the range studied 1%Pd/TiO2 catalyst achieved 86.4% conversion of phenol to CO2 in a standard batch-slurry system utilizing UV. However under recycle or continuous operation Pd leaching from catalyst surface led to gradual deactivation. Au-Pd nanoparticles supported on TiO2 P25 were stable and recyclable, here Au species were found to help to anchor Pd species on TiO2, and no observable Pd leaching occurred. Utilizing UV, 1%Pd/TiO2 showed faster rate of phenol degradation in comparison to Au-Pd/TiO2, while 1%Au/TiO2 and 0.5%Au-0.5%Pd/TiO2 showed faster phenol degradation rates under visible light. The TiO2 P25 support was also found to be active, stable and recyclable in phenol degradation utilizing UV; and was hence considered suitable for continuous operation. However poor oxygen mass transfer led to the formation and lay-down of polymeric species when using a Trickle bed approach. Operation in the Taylor flow regime was demonstrated to increase oxygen saturation and significantly reduced deactivation. Hence continuous photocatalytic degradation of phenol could be achieved using TiO2 under Taylor Flow conditions.